Program Pendampingan Kemasan Pangan bagi Tenant melalui Pusat Pengembangan Wirausaha Bioindustri - Hermawan Seftiono; Maulidian Maulidian; Inanpi Hidayati Sumiasih; Mutiara Dewi Puspitawati (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2021)
Food Packaging Assistance Program for Tenants through the Bioindustry Entrepreneur Development Center Packaging is very important, especially on attracting consumer interest, so it needs to be adjusted based on market segments, because consumer tastes of products can be seen from the packaging. Generally, tenants already have packaging, but it was very simple, just mention the name of the product. Therefore, this mentoring program would increase awareness of tenants to make packaging based on labelling regulation for food products. The stages on this community service activity included provision of food packaging, presenting some packaging samples and assisting also giving consultation for tenant about food product packaging. This mentoring activity provided many benefits for tenants. There were 12 tenants participated on this activity. About 80% of participants got improve for their package, on design also information which required on the packaging.